Effects of ESG activity recognition factors on innovative organization culture, job crafting, and job performance - Minsuck Jin; Bo-Young Kim (Administrative Sciences, 2022)
This study aims to verify the effects of organizational members' ESG activity recognition on job performance with the mediation of innovative organizational culture and job crafting. To this end, a questionnaire survey was carried out based on previous studies, and 237 questionnaire response copies were analyzed. An empirical study was conducted on the effects of each ESG activity recognition factor on job performance with the mediation of innovative organizational culture and job crafting. According to the analysis result, the society factor had a positive (+) effect on innovation-oriented culture among the ESG activity recognition factors, the environment factor had a negative (-) effect, and the governance factor did not have any effect. In contrast, governance had a positive (+) effect on relationship-oriented culture in innovative organizational culture. However, the environment and societal factors did not have any effect. The innovation-oriented culture and relationship-oriented culture directly affected job crafting, but they were confirmed not to have a direct effect on job performance. Hence, the result shows that the ESG activity recognition's society factor reinforces innovative organizational culture, and the governance factor can consolidate organizational relationships.
Keywords: 350; ESG activity recognition; ESG management; innovative organization culture; job crafting; job performance